Prayōt sūngsut kh̨ōng chīwit nī - Phra Thēpwēthī (Prayut) (s.n., 1987)
On Buddhist philosophy; volume brought out on occasion of 60th royal birthday anniversary of Bhumibol Adulyadej, King of Thailand, b. 1927.